The handbook of conflict resolution : theory and practice - Deutsch, Morton, 1920-; Coleman, Peter T., 1959-; Marcus, Eric Colton (San Francisco, CA : Jossey-Bass, 2006)
"Written for both the professional and the student just learning the art of mediation and conflict resolution, the book contains many useful ideas and practical suggestions for understanding and managing conflicts of all sorts: interpersonal, intergroup, and international. The Handbook covers a broad range of topics including information on cooperation and competition, justice, trust development and repair, resolving intractable conflict, and working with culture and conflict."--BOOK JACKET.
Introduction / Morton Deutsch -- 1. Cooperation and Competition / Morton Deutsch -- 2. Justice and Conflict / Morton Deutsch -- 3. Constructive Controversy: The Value of Intellectual Opposition / David W. Johnson, Roger T. Johnson and Dean Tjosvold -- 4. Trust, Trust Development, and Trust Repair / Roy J. Lewicki and Carolyn Wiethoff -- 5. Power and Conflict / Peter T. Coleman -- 6. Communication and Conflict / Robert M. Krauss and Ezequiel Morsella -- 7. Persuasion in Negotiations and Conflict Situations / Shelly L. Chaiken, Deborah H. Gruenfeld and Charles M. Judd -- 8. Intergroup Conflict / Ronald J. Fisher -- 9. Problem Solving and Decision Making in Conflict Resolution / Eben A. Weitzman and Patricia Flynn Weitzman -- 10. Judgmental Biases in Conflict Resolution and How to Overcome Them / Leigh Thompson and Janice Nadler -- 11. Anger and Retaliation in Conflict: The Role of Attribution / Keith G. Allred -- 12. Self-Regulation in the Service of Conflict Resolution / Walter Mischel and Aaron L. DeSmet -- 13. Process and Outcome Goal Orientations in Conflict Situations: The Importance of Framing / Tal Y. Katz and Caryn J. Block -- 14. Personality and Conflict / Sandra V. Sandy, Susan K. Boardman and Morton Deutsch -- 15. The Development of Conflict Resolution Skills in Children: Preschool to Adolescence / Sandra V. Sandy and Kathleen M. Cochran -- 16. Creativity and Conflict Resolution: The Role of Point of View / Howard E. Gruber -- 17. Some Guidelines for Developing a Creative Approach to Conflict / Peter T. Coleman and Morton Deutsch -- 18. Change Processes and Conflict / Eric C. Marcus -- 19. Learning Through Reflection / Victoria J. Marsick and Alfonso Sauquet -- 20. Aggression and Violence / Susan Opotow -- 21. Intractable Conflict / Peter T. Coleman -- 22. Culture and Conflict / Paul R. Kimmel -- 23. Cooperative and Competitive Conflict in China / Dean Tjosvold, Kwok Leung and David W. Johnson -- 24. Teaching Conflict Resolution Skills in a Workshop / Ellen Raider, Susan Coleman and Janet Gerson -- 25. Mediation / Kenneth Kressel -- 26. Managing Conflict Through Large-Group Methods / Barbara Benedict Bunker -- 27. A Framework for Thinking About Research on Conflict Resolution Training / Morton Deutsch -- Concluding Overview / Peter T. Coleman.
Includes bibliographical references and index.
Keywords: Conflict management; Conflict (Psychology); Interpersonal Relations; Conflictmanagement; Wedijver; Bemiddeling; Probleemoplossing; Communicatie